Karakteristik Sosial EKonomi Petani Kelapa (Cocos Nucifera) Studi Kasus Desa Labuang Kecamatan Namrole Kabupaten Buru Selatan - Nurlatu, Stewar; Pattiselanno, August E; Lawalata, Marfin (KOMUNITAS: Jurnal Ilmu Sosiologi, 2025)
This study aims to analyze the socio-economic characteristics of coconut farmers and the factors influencing coconut farming productivity in Labuang Village, Namrole District, South Buru Regency. The research was conducted over one month using a descriptive qualitative method with a census approach, where all 30 coconut farmers in the village were selected as respondents. The research location was determined purposively, as Labuang Village has the largest coconut plantation area in the district. Data were collected through interviews using questionnaires and secondary data from relevant agencies. The results showed that most farmers had 10–20 years of farming experience, elementary school education, more than four dependents, and cultivated land areas ranging from 0.5 to 1.28 hectares with production volumes of 400–800 kg. Productivity was calculated based on yield per hectare, and the influencing factors were analyzed using a regression function. The findings indicated that social, economic, and sustainability factors contributed to productivity, with respective scores of 8–9, 11–12, and 9–11. Farmers’ income ranged between Rp. 5,000,000 and Rp. 12,000,000.